Model Manajemen Big Data Komoditas Beras untuk Kebijakan Pangan Nasional - Feriadi; Eneng Tita Tosida; Fajar Delli Wihartiko; Irman Hermadi; Yani Nurhadryani (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
Rice is the main commodity in Indonesia, both for consumption and production. Rice production data are available at the Badan Pusat Statistika and at Kementrian Pertanian. The data is used to build a large data management model for Indonesia's rice trade. The model development strategy is done through analyzing agriculture big data analytic that is equipped with descriptive analysis, evaluation, predictive and prescriptive. The models and designs that are built discuss business processes, stakeholder networks and network management. Descriptive analysis results in the form of grouping and visualization of rice data. The results of the diagnostic process using classification approach produce a decision tree to see the results of the level of production in a province. In the predictive process produces a linear regression model to predict the results of the following year's production as well as in the analysis.